Overconfidence and career choice - Jonathan F. Schulz; Christian Thöni (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2014)
People self-assess their relative ability when making career choices. Thus, confidence in own abilities is likely an important factor for selection into various career paths. In a sample of 711 first-year students we examine whether there are systematic differences in confidence levels across fields of study. We find evidence for selection based on our experimental confidence measure: While Political Science students exhibit the highest confidence levels, students of Humanities range at the other end of the scale. This may have important implications for subsequent earnings and/or professions students select themselves in.
Keywords: C91; I21; J24; 330; overconfidence; selection; field of study; career choice